2(x-3)+3(4-x)=53+2x ​



Odpowiedź :

Pepcco
Odpowiedź w załączniku
Zobacz obrazek Pepcco

Odpowiedź:

2 ( x-3) + 3 ( 4-x) = 53 + 2x

2x-6 +12 -3x = 53 +2x

  2x-2x -3x= 53 -12 +6

-3x=  47  /: 3

  x= - 15 i 2/3

 spr...   2* (-47/3) -6 +12 -3 *(-47/3) = 53 + 2*(-47/3)

                -94/3 -6 +12 +141/3= 53 -94/3

                   -31 i 1/3 -6 +12 +47 = 53 - 31 i 1/3

                   -37 i 1/3  + 59 = 21 i 2/3

                             21 i 2/3 = 21 i 2/3

                                L=P

Szczegółowe wyjaśnienie: